Pelaksanaan Jaminan Sosial Kecelakaan Kerja pada Pekerja Toko Modern (Supermarket) di Kabupaten Badung - I Made Oka Pradnya Prawira; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2019)
Guarantee of work accident was an assurance given by workers in the form of money in lieu of the cost of freight, the cost of the inspection, the cost of medicine, as a result of a work accident. Against workers who had an accident at work is entitled to a guarantee of work accident. Based on the information in the field that occurs in the Risaldi Supermarket in Badung Regency has occurred that the Supermarket Risaldi Mart as entrepreneurs have yet to provide full protection of the law against the workers who were put to work. Is there any formula issues namely (1) How the implementation of a social security worker accident at Modern Store in Badung Regency? (2) Factors that become obstacles to Modern Stores not requiring workers in the social security program work accident Badung Regency? The research used in this thesis is the empirical research. Because in this study investigated people in a relationship are living in the community then the empirical legal research methods can be said to be a sociological legal research. Participants of the BPJS employment will get a special guarantee if a work accident, such as rehabilitation, health care, returns to work program (return to work), compensation for death and funeral expenses, as well as the workers will get Promote and preventive activities to support the realization of safety and occupational health. In the implementation of social security in the modern shop is still the lack of thoroughness of the worker in the complete warranty claim requirements work accident before it is given to the BPJS so take a long time in the process of dilution and lack of attention toward the payment of compensation to workers who have been stricken work accident.